Milk Chemical Composition of Dairy Cows Fed Rations Containing Protected Omega-3 Fatty Acids and Fermented Rice Bran - . Sudibya; S H Purnomo (Faculty of Animal Science, Bogor Agricultural University, 2013)
The research was conducted to investigate the effect of ration containing protected omega-3 and fermented rice bran on chemical composition of dairy milk. The research employed 10 female PFH dairy cows of 2-4 years old with body weight 300-375 kg. The research was assigned in randomized complete block design. The treatment consisted of P0= control ration, P1= P0 + 20% fermented rice bran, P2= P1 + 4% soya bean oil, P3= P1 + 4% protected tuna fish oil and P4= P1 + 4% protected lemuru fish oil. The results showed that the effects of fish oil supplementation in the rations significantly (P<0.01) decreased feed consumption, cholesterol, low density lipoprotein, lipids, and saturated fatty acids. Meanwhile, it increased milk production, content of high density lipoprotein, omega-3, omega-6 and unsaturated fatty acids in the dairy cows milk. It is concluded that the inclusion of 4% protected fish oil in the rations can produce healthy milk by decreasing milk cholesterol and increasing omega-3 fatty acids content.